2018
DOI: 10.1007/s00221-018-5219-1
|View full text |Cite
|
Sign up to set email alerts
|

Increased enslaving in elderly is associated with changes in neural control of the extrinsic finger muscles

Abstract: Aging has consequences for hand motor control, among others affecting finger force enslaving during static pressing tasks. The aim of this study was to assess whether the extent of finger force enslaving changes with aging during a task that involves both static and dynamic phases. Ten right-handed young (22–30 years) and ten elderly subjects (67–79 years) were instructed to first exert a constant force (static phase) and then flex their index finger while counteracting constant resistance forces orthogonal to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Our findings also suggest an age-related decline in motor inhibition: longer release duration (during tracking) and reduced finger individuation, both considered to involve processes of motor inhibition ( 31 , 64 , 65 ), were found in elderly subjects and those with cognitive decline. Age-related increase in release duration has been reported previously in healthy subjects ( 62 ), whereas altered finger individuation has not been shown consistently ( 27 , 66 ), probably due to task-related differences. Our tapping task, resembling keyboard typing or piano playing, revealed evidence for a similar reduction of independent finger movements in elderly subjects and, in subjects with cognitive decline.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Our findings also suggest an age-related decline in motor inhibition: longer release duration (during tracking) and reduced finger individuation, both considered to involve processes of motor inhibition ( 31 , 64 , 65 ), were found in elderly subjects and those with cognitive decline. Age-related increase in release duration has been reported previously in healthy subjects ( 62 ), whereas altered finger individuation has not been shown consistently ( 27 , 66 ), probably due to task-related differences. Our tapping task, resembling keyboard typing or piano playing, revealed evidence for a similar reduction of independent finger movements in elderly subjects and, in subjects with cognitive decline.…”
Section: Discussionmentioning
confidence: 70%
“…Studies have reported age-related impairments in maximal grip force ( 18 ) sensory functioning ( 19 , 20 ) and in grasping and manipulation of objects [Box and Block test ( 21 , 22 ), NHPT ( 23 , 24 )]. Regarding specific manual dexterity components, accuracy in force control tasks is reduced in age ( 25 , 26 ) and independence of finger movements may deteriorate ( 27 ). Increased variability of finger movements ( 28 ) and motor slowing ( 29 ) have also been documented.…”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast to our results, in which enslaving was found to be higher and the range of independent movement was lower, especially for index finger flexion, for the elderly compared to the younger subjects. In a recent study from our group, higher force enslaving in elderly was also found during a static finger pressing task (Mirakhorlo et al 2018). The opposite outcomes compared to most previous studies were explained by not restraining the arm and wrist.…”
Section: Changes In Finger Independencementioning
confidence: 63%
“…In the present experiment, the wrist was not secured to the setup. As a consequence, part of the activity of the extrinsic finger flexors and extensors may be related to stabilization of the wrist and not to the finger movements (Mirakhorlo et al 2018). When the wrist is fixed, the function of these muscles is limited to solely produce finger movements.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation